Development of therapeutic PD-1 monoclonal antibodies for treatment of canine tumor - Jinquan He; Xuan Yin; Anqi Xie; Ning Wang; Zeming Guo; Yizhou Chen; Weidong Cui; Xueqiao Qian; Chungen Pan (Veterinary Immunology and Immunopathology, 2026)

A metabolism-driven multifunctional hydrogel promotes adipocyte differentiation and reduces fibrotic skin repair - Zhangrui Wu; Liping Zhang; Yi Wang; Zixuan Feng; Zeming Zhuang; Xincao Zhong; Chunye Chen; Xiaoying Lin; Yong Wang; Xuewen Wang; Kai Guo; Jun Chen; et al. (Chemical Engineering Journal, 2026)

Study on the adsorption of phosphorus from phosphorus-containing wastewater using composite mineral-based adsorbent materials derived from phosphate tailing - Yihuai Su; Hongwei Wei; Ting Xu; Zeming Shi; Chengwen Wang (Minerals Engineering, 2026)

Non-additive effects of microplastics, atrazine, and sulfamethoxazole co-exposure on Penaeus vannamei health and environmental risks - Yinan Wang; Qiangqiang Shi; Weijia Gan; Feng Xu; Hao Liu; Liuquan Zhang; Rongrong Zhang; Jiong Chen; Zeming Zhang; Xizhi Shi (Journal of Hazardous Materials, 2026)

LncRNA TUG1 promotes hypertrophic scar formation via the miR-627/IGF1R axis - Zeming Bai; Ziyang Han; Xiangzi Kong; Rirui Zhao; Haiwei Sun; Hai Huang; GuYue Wang; Zhe Li; Kai Tao; Jiulong Liang (Journal of Molecular Histology, 2026)
Hypertrophic scars (HS) are fibrotic skin disorders driven by abnormal fibroblast activity. The molecular mechanisms underlying HS remain incompletely understood, particularly the role of non-coding RNAs. Expression levels of lncRNA TUG1, miR-627, and IGF1R were measured in HS tissues and fibroblasts using qRT-PCR and Western blotting. Dual-luciferase assays validated direct interactions. Functional effects of TUG1 and miR-627 on fibroblast proliferation and migration were assessed using MTT and Transwell assays. A rabbit ear model of HS was used to examine in vivo effects of TUG1 and miR-627 modulation on scar formation and molecular expression. TUG1 was significantly upregulated in HS tissues and inversely correlated with miR-627, which was downregulated. TUG1 promoted fibroblast proliferation and migration by directly sponging miR-627, thereby lifting repression on IGF1R, a known pro-fibrotic effector. Luciferase assays confirmed direct binding of miR-627 to both TUG1 and IGF1R. Co-transfection of miR-627 attenuated TUG1-induced IGF1R upregulation and reversed its pro-fibrotic cellular effects. In vivo, TUG1 overexpression led to increased scar thickness, collagen deposition, and IGF1R expression, while miR-627 overexpression mitigated these effects. Co-administration of both restored scar morphology and molecular markers to near-control levels. TUG1 promotes hypertrophic scar formation by sponging miR-627 and derepressing IGF1R. This newly identified TUG1–miR-627–IGF1R axis plays a central role in HS pathogenesis and may serve as a promising therapeutic target for fibrotic skin disease.

Causal Transformer for Learning Embeddings from Structured Medical History Records and Multi-Source Data Integration for Complex Disease Risk Prediction - Zeming Li; Yu Xu; Debajyoti Chowdhury; Hip Fung Yip; Chonghao Wang; Lu Zhang (Interdisciplinary Sciences: Computational Life Sciences, 2026)
Traditional disease risk prediction models predominantly rely on statistical algorithms and often focus on genetic factors or a limited set of lifestyle factors to estimate the risk of disease onset. Recently, more comprehensive approaches have emerged that integrate genetic factors with additional lifestyle factors (e.g., alcohol intake) and physical features (e.g., body mass index, age) to increase predictive accuracy. Since the onset of complex diseases is often accompanied by the occurrence of comorbidities, incorporating medical history records is a critical yet underexplored avenue for improving risk prediction. In this study, we propose a novel framework, MIDRP (Multi-source Integration for Disease Risk Prediction), which incorporates genetic variants, lifestyle factors, physical attributes, and medical history records to achieve more robust and accurate predictions. At the heart of our approach lies a causal Transformer architecture, specifically designed to extract and interpret nuanced patterns from medical history records. In the experiments, we compared MIDRP with several baselines, including LDPred2, random forest, multilayer perception, logistic regression, AdaBoost, DiseaseCapsule, EIR, and Med-Bert, on three complex diseases Coronary Artery Disease, Type 2 Diabetes, and Breast Cancer using data from the UK Biobank. Our method achieved state-of-the-art performance, AUROC scores of 0.783, 0.841, and 0.784, respectively, demonstrating its potential in the field of complex disease risk prediction.

Dynamic mesh-based investigation of thermal environment during mars ascent vehicle launch phase - Zhongyi Sun; Zhanxun Che; Chengeng Zhao; Zeming Wang; Guigao Le (Advances in Space Research, 2026)

SynCom improves carbon fixation capacity in phenanthrene-contaminated soils by reshaping microbial communities - Youai Zhang; Mengyao Wang; Lingyu Zhang; Wenjie Li; Wanting Ling; Zeming Wang; Ahmed Mosa; Yanzheng Gao (Journal of Environmental Management, 2026)

Performance study on a cryogenic bubble pump for low-flow-rate liquid nitrogen transfer - Yuhui Chen; Ya Xu; Daming Sun; Zeming Wang; Qie Shen (International Journal of Refrigeration, 2026)

Spatio-temporal variations of heavy metal(loid)s and their influencing factors in surface sediments of Daya Bay, South China Sea - Zeming Wang; Nan Zheng; Man Hao; Yahui Xu; Jinmei Li (Frontiers in Marine Science, 2026)
To elucidate the spatiotemporal dynamics and driving mechanisms of heavy metal (loid)s (HMs) in coastal systems, this study investigated the surface sediments from Daya Bay across four seasons. Results indicated that the average HM concentrations (mg/kg) decreased in the order of Zn (65.35) > Pb (28.66) > Cu (13.19) > As (7.06) > Hg (0.073) > Cd (0.058), with Pb, As and Hg exhibiting significant seasonal heterogeneity ( p < 0.05). The Geo-accumulation Index ( I geo ) and Contamination Factor identified Hg as the dominant contaminant, registering the highest average I geo value of 2.039. Overall, the surface sediments in the study area exhibited a moderate level of cumulative pollution with an average Pollution Load Index (PLI) of 2.48, following a seasonal decline of winter (2.76) > spring (2.49) > autumn (2.39) > summer (2.27). Crucially, Redundancy Analysis revealed that the distribution of Cu, Zn, Cd, and Pb was primarily governed by natural physicochemical binding to fine-grained, organic-rich matrices. In contrast, the accumulation of Hg and As exhibited a stronger dependency on dynamic biogeochemical factors, notably dissolved oxygen and anthropogenic nutrient inputs. These findings highlight the necessity of distinct management strategies that account for the coupling between sediment matrices and water column biogeochemistry.

Customizable sub-nanometer vertical-step grayscale lithography - Haonan Ma; Shijie Zhao; Xia Liu; Ziying Hu; Xu Han; Hongtao Li; Zeming Jin; Mingdi Zhang; Jixiang Li; Wenke Fu; Yunyun Dai; Yuan Huang; et al. (Science Bulletin, 2026)

Posttranslational regulation of TOR kinase activity controls resource allocation between plant growth and immunity in Arabidopsis - Jianwei Li; Ran Wang; Chenying Li; Xijie Guo; Qinghong Li; Zhixuan Wu; Shanshan Zeng; Fan Qi; Yuchen Wang; Zhiyi Jia; Weiwei Yu; Zeming Huang; et al. (Molecular Plant, 2026)

Melatonin alleviates Li toxicity in wheat via regulating redox and K+ homeostasis - Waqas ud Din Khan; Lei Wang; Zeming Xing; Sergey Shabala; Mohsin Tanveer (Journal of Hazardous Materials, 2026)

17β-estradiol-induced growth–defense tradeoffs in pak choi (Brassica) and implications for intake risk - Yang Chen; Junyue Wang; Zikang Zhang; Zeming Wang; Youai Zhang; Yanzheng Gao; Chao Qin; Wanting Ling (Journal of Environmental Management, 2026)

Ethanol-induced stable dispersion and compatibility of MXene in WEP leading to highly ordered layered materials for high electromagnetic interference shielding performance - Yingfan Li; Bohan Ding; Xiaoyan Ma; Yongjie Bi; Zeming Jin; Yue Sun; Jinghe Guo; Yanxiang Wang; Chao Teng (Chemical Engineering Journal, 2026)

Analysis of the fire evolution process of an electric vehicle in a confined garage - Liang Yin; Ruichao Wei; Liang Zhang; Shaozhang Chen; Zeming Ren; Zongcun Wang; Shenshi Huang (Tunnelling and Underground Space Technology, 2026)

Non-directly bonded single-atom pairs towards H2/CO electrooxidation - Tongtong Yang; Heng Liu; Hengjie Liu; Weiyi Zhao; Jiawei Ge; Wenhui Wang; Shuai Yang; Meijian Tang; Kai Wei; Kangcheng Wang; Zeming Qi; Xian Wang; et al. (Science Bulletin, 2026)

Pathogen-induced H2O2 triggers phosphorylation of the RNA-binding protein RRM2R to suppress OsMAPKKK18 intron retention for orchestrating rice immunity and growth - Xiang Lu; Yibang An; Wenxiu Lu; Jing Li; Qing Xiong; Miaomiao Zhu; Yao He; Jia Yang; Yue Wang; Zeming Zhang; Xiaorong Gong; Yulong Qian; et al. (Molecular Plant, 2026)

Feedstock loading and pressure synergy in high-solid microalgae HTL: Boosting bio-oil yield while reducing nitrogen content - Zhicong Wang; Zeming Zhao; Collins Chimezie Elendu; Peigao Duan (Biomass and Bioenergy, 2026)

Engineering shape memory paper with superior strength, thermal stability, and recyclability through polyimide sizing - Qiang Wang; Zeming Zhang; Zihao Wang; Dehai Yu; Hui Gao; Shanshan Liu; Xingxiang Ji; Zhanhui Yuan (Chemical Engineering Journal, 2025)

Using degrading endophytic bacteria to detoxify the phthalic acid esters in crops from contaminated soil - Xiangyu Liu; Xiangrui Du; Xiangzhi Zuo; Zeming Wang; Bozena Czech; Patryk Oleszczuk; Yanzheng Gao (Journal of Environmental Sciences, 2025)

Extremely high toxicity of gaseous intermediate/semi volatile organic compounds emitted from typical incomplete biomass burning in China - Yueqian Wang; Di Wu; Zihua Guo; Xiu Chen; Yang Li; Yifei Tan; Zeming Ye; Yuzhe Liu; Yaoqiang Huo; Qing Li; Jianmin Chen (Journal of Hazardous Materials, 2025)

KC1036, a multi-kinase inhibitor with anti-angiogenic activity, can effectively suppress the tumor growth of Ewing sarcoma - Xuejin Ou; Ge Gao; Qizhi Ma; Diyuan Qin; Kai Li; Mingyang Feng; Yu Gao; Yao Zeng; Yue Chen; Xia He; Ting Zhang; Zeming Mo; et al. (Angiogenesis, 2025)

Identification of Mitochondrial and Succinylation Modification-Related Gene Signature in Ischemic Stroke - Lixia Wang; Jishuai Zhao; Hui Cai; Xiaoling Ying; Yonglei Liu; Zeming Luo; Heyan Chen; Lin Yang (Molecular Neurobiology, 2025)

Development and swallowability evaluation of easy-to-swallow anthocyanin-loaded ROS-responsive hydrogels - Yumeng Wang; Siyi Tang; Meili Xin; Zhiying Li; Guoli Ao; Xu Xie; Yihan Li; Zijing Li; Zeming Wang; Xilin Wu; Jinlong Tian; Bin Li (Innovative Food Science & Emerging Technologies, 2025)

Improvement of dehydrogenation kinetics of MgH2 with VMnFeCoNi high-entropy alloy - Yingjie Wang; Dianchen Feng; Wenfeng Meng; Qiuzhuo Nie; Tingting Zhai; Zeming Yuan; Yanghuan Zhang (Fuel, 2025)

Causes and influencing mechanisms of differences in phosphorus occurrence forms in sediments of different types of urban lakes - Yinghai Zhu; Zeming Shi; Qian Li; Chengjie Zou; Na Zhang; Xinyu Wang; Kai Zhao (Science of The Total Environment, 2025)

Co-exposure to enrofloxacin and atrazine enhances the hepatotoxicity in Larimichthys crocea by targeting the hypothalamic–pituitary–thyroid and gut–liver axes - Yinan Wang; Chenxue Yang; Qiangqiang Shi; Liuquan Zhang; Hao Liu; Jinjie You; Rongrong Zhang; Aili Sun; Suquan Song; Zeming Zhang; Xizhi Shi (Journal of Hazardous Materials, 2025)

Highly selective electrosynthesis of hydrogen peroxide with tellurium nanoparticles encapsulated in ultrathin graphitic carbon shells - Zeming Wang; Huazhang Guo; Shihao Zhang; Jiye Zhang; Liang Wang (Chemical Engineering Journal, 2025)

Enhancing hydrogen storage performance by N-doping induced chemical and structural effects in porous carbon materials - Zeming Zhong; Xue Gao; Liangjun Huang; Hui Wang; Yujun Zhao; Min Zhu (Chemical Engineering Journal, 2025)

Geographical impact on the distribution of polycyclic aromatic hydrocarbons (PAHs) in hilly terrain topsoil: A case study at Chongqing, SW, China - Jianghai Liao; Xinyu Wang; Hangjia Wang; Mingcai Hou; Sizhuo Zhou; Zeming Shi; Yuxiang Zhan; Shijun Ni; Ruilin Wang (Journal of Hazardous Materials, 2025)

Accumulation patterns and chronic toxic effects of triphenyl phosphine in Mytilus coruscus - Ningbo Wang; Yinan Wang; Rongrong Zhang; Aili Sun; Yin Lu; Zeming Zhang; Xizhi Shi (Aquaculture, 2025)

Unraveling the pharmaceutical footprint and risks of combining different aquaculture modes and tailwater treatment systems - Feng Xu; Yangcai Wang; Qiangqiang Shi; Yinliang Wu; Zeming Zhang; Xizhi Shi (Aquaculture, 2025)

Analysis of potential human accumulation differences and mechanisms of environmental new flame retardants: Based on in vitro experiments and theoretical calculations - Junchao Ma; Chao Qin; Juan Yan; Chunyu Wang; Yu Liu; Zeming Wang; Zekai Li; Yanzheng Gao (Science of The Total Environment, 2025)

Mn oxide-modified biochars with high adsorption capacity for Pb(II) in wastewater: Preparation and adsorption mechanisms - Jiabo Wang; Hongxia Zhu; Yue Hu; Laigang Hu; Zeming Wei; Yan Ying Li; Xinglu Hu (Environmental Research, 2025)

Methods and mechanisms for enhancing the water retention properties of Jiuzhaigou disintegrated rubble soils - Zeming Wei; Hongchao Xi; Xiangjun Pei; Xiaochao Zhang; Mao Qiu; Tiao Huang; Zhaocheng Wang; Junlian Jiang; Jie Du; Daijun Jian (Journal of Mountain Science, 2025)

The Role of MicroRNA-206 in the Regulation of Diabetic Wound Healing via Hypoxia-Inducible Factor 1-Alpha - Zeming Bai; Dapeng Zhou; Kai Tao; Feng Lin; Hongyi Wang; Haiwei Sun; Ruidi Liu; Zhe Li (Biochemical Genetics, 2025)
Successful wound healing in diabetic patients is hindered by dysregulated miRNA expression. This study aimed to investigate the abnormal expression of miRNAs in diabetic wound healing and the potential therapeutic role of modulating the miR-206/HIF-1α pathway. MicroRNA assays were used to identify differentially expressed miRNAs in diabetic wound sites and adjacent areas. In vitro models and a rat diabetic model were established to evaluate the effects of miR-206 on HIF-1α regulation and wound healing. The study revealed differential expression of miR-206 in diabetic wound tissues, its interaction with HIF-1α, and the inhibitory effect of miR-206 on cell growth under high glucose conditions. Modulating the miR-206/HIF-1α pathway using miR-206 antagomir promoted HIF-1α, CD34, and VEGF expression, ultimately enhancing diabetic wound healing.

Combined ecotoxicity of polystyrene microplastics and Di-(2-ethylhexyl) phthalate increase exposure risks to Mytilus coruscus based on the bioaccumulation, oxidative stress, metabolic profiles, and nutritional interferences - Yinan Wang; Qiangqiang Shi; Menglan Zhang; Lingyan Xu; Qiang Wei; Rongrong Zhang; Aili Sun; Yin Lu; Zeming Zhang; Xizhi Shi (Journal of Hazardous Materials, 2024)

Insights into oral lentinan immunomodulation: Dectin-1-mediated lymphatic transport from Peyer's patch M cells to mononuclear phagocytes - Kaiping Wang; Yuxuan Liu; Zeming Zhang; Ziming Zheng; Wenqi Tang; Wangtianzi Teng; Xu Mu; Jinglin Wang; Yu Zhang (Carbohydrate Polymers, 2024)

Machine learning-based surrogate models for fast impact assessment of a new building on urban local microclimate at design stage - Zeming Zhao; Hangxin Li; Shengwei Wang (Building and Environment, 2024)

Benthic sediment nitrogen transformation processes in Arctic Kongsfjorden subject to glacier discharge - Mengjie Guo; Qing Wang; Wanying Zhang; Yi Jiao; Zeming Zhou; Lijun Hou; Renbin Zhu (Polar Biology, 2024)

Hydrophobic carbon quantum dots with Lewis-Basic nitrogen sites for electrocatalyst CO2 reduction to CH4 - Shuai Fu; Bijun Tang; Zeming Wang; Guangbin An; Mingwan Zhang; Kang Wang; Wenhui Liu; Huazhang Guo; Baohua Zhang; Liang Wang (Chemical Engineering Journal, 2024)

Accumulation and growth toxicity mechanisms of fluxapyroxad revealed by physiological, hepatopancreas transcriptome, and gut microbiome analysis in Pacific white shrimp (Litopenaeus vannamei) - Ningbo Wang; Rongrong Zhang; Yinan Wang; Liuquan Zhang; Aili Sun; Zeming Zhang; Xizhi Shi (Journal of Hazardous Materials, 2024)

Creating comfortable outdoor environments: Understanding the intricate relationship between sound, humidity, and thermal comfort - Zeming Qin; Bairu Lu; Wenqiang Jing; Yingdi Yin; Lefang Zhang; Xinqi Wang; Wei Luo; Jin Zhang; Jing Qiu; Yuting Dong (Urban Climate, 2024)

The Arabian Sea and Bay of Bengal play a key role in extreme precipitation during the snow season over the Tibetan Plateau - Weiguo Wang; Hongyi Li; Zeming Xie; Xiaohua Hao; Jian Wang (International Journal of Climatology, 2024)
Water vapour is a critical component of the hydrological cycle and plays a key role in climate systems and water resources on the Tibetan Plateau (TP). However, the effect of water vapour on extreme precipitation during the snow season over the TP, where snow cover is widespread, has not been determined. In this study, we investigated the water vapour contributions from extreme precipitation events during the snow season from 1980 to 2017 in four subregions of the TP using the flexible particle dispersion method. We divided the TP into four regions: the northeastern TP (NETP), northwestern TP (NWTP), southeastern TP (SETP) and southwestern TP (SWTP). The water vapour contributions from extreme precipitation among the four subregions were clearly different. The most important water vapour area that contributed the most water vapour to extreme precipitation over the NETP was from local contributions; nevertheless, Central Asia contributed the most water vapour to the NWTP. Water vapour from the Arabian Sea and Bay of Bengal (ASBB) dominantly controlled extreme precipitation in the SETP at a ratio of 45% and in the SWTP at a ratio of 72.9%. The water vapour contribution from the ASBB was significantly correlated with the extreme precipitation occurring in the TP subregions during the snow season in comparison to that of non‐extreme precipitation. These results could improve the understanding of water vapour cycle differences across the interior TP; additionally, our study provides a theoretical reference for the relationship between the snow distribution and water vapour sources in the TP.

A RRT based path planning scheme for multi-DOF robots in unstructured environments - Meilin Kang; Qinhu Chen; Zeming Fan; Chuan Yu; Yixin Wang; Xiaojun Yu (Computers and Electronics in Agriculture, 2024)

Mangrove plants are promising bioindicator of coastal atmospheric microplastics pollution - Yuanyin Huang; Ziying Zhu; Tianmu Li; Minqian Li; Zeming Cai; Xiaocui Wang; Han Gong; Muting Yan (Journal of Hazardous Materials, 2024)

Effects of coal-fired power plants on soil microbial diversity and community structures - Bowen Sun; Renbin Zhu; Yu Shi; Wanying Zhang; Zeming Zhou; Dawei Ma; Runfang Wang; Haitao Dai; Chenshuai Che (Journal of Environmental Sciences, 2024)

Comparative antioxidant and metabolomic analysis for the identification of differential response of mussel (Mytilus coruscus) to four succinate dehydrogenase inhibitor fungicides - Ningbo Wang; Zeming Zhang; Yinan Wang; Liuquan Zhang; Aili Sun; Hua Liu; Xizhi Shi (Environmental Science and Pollution Research, 2024)

Accumulation and elimination properties and comparative toxicity of fluxapyroxad in juvenile and adult large yellow croaker (Larimichthys crocea) - Ningbo Wang; Yinan Wang; Aili Sun; Zeming Zhang; Xizhi Shi (Science of The Total Environment, 2024)

Spatial-temporal evolution of ecological risks in a typical urban lake in Southwestern China - Yinghai Zhu; Zeming Shi; Xinyu Wang; Chengjie Zou; Na Zhang; Peijia Zheng; Jianming Wang; Yu Wang (Journal of Cleaner Production, 2024)

Flexural behavior of wet panel-to-panel groove-and-tongue joints provided with lapped U-bars - Ao Dong; Zhenyu Li; Bin Rong; Changxiang Wang; Zeming Wang; Hui Xu (Engineering Structures, 2024)

Combined effects of microplastics and antibiotic-resistant bacteria on Daphnia magna growth and expression of functional genes - Xiaofeng Chen; Xiaocui Wang; Yuanyin Huang; Ziying Zhu; Tianmu Li; Zeming Cai; Minqian Li; Han Gong; Muting Yan (Science of The Total Environment, 2023)

Suppressing hydrogen evolution and eliminating sulfation in lead-carbon batteries via potential-matching g-C3N4@rGO nanosheets - Daiwen Tao; Xiong Liu; Simiao Huang; Zeming Li; Hui Yang; Jinyu Wang; Qilong Zhang (Chemical Engineering Journal, 2023)

Toxic effects of three perfluorinated or polyfluorinated compounds (PFCs) on two strains of freshwater algae: Implications for ecological risk assessments - Liangliang Zhang; Xiaowei Zheng; Xianglin Liu; Jue Li; Yanyao Li; Zeming Wang; Nan Zheng; Xiangrong Wang; Zhengqiu Fan (Journal of Environmental Sciences, 2023)

Geothermal springs with high δ13CCO2-DIC along the Xianshuihe fault, Western Sichuan, China: A geochemical signature of enhanced deep tectonic activity - Jinlong Liang; Yi Yu; Zeming Shi; Zhipeng Li; Yi Huang; Hao Song; Jinyong Xu; Xinyu Wang; Xiaocheng Zhou; Luyu Huang; Zebin Luo; Jue Tong; et al. (Journal of Hydrology, 2023)

Chain-mediating effect of interaction between telomeres and mitochondria under oxidative stress in coke oven workers - Zhiguang Gu; Zeming Niu; Zhaofan Yan; Yahui Fan; Jing Sun; Xiangkai Zhao; Xiaoran Duan; Wu Yao; Yongli Yang; Wei Wang (Environmental Pollution, 2023)

Environmental health risks induced by interaction between phthalic acid esters (PAEs) and biological macromolecules: A review - Zeming Wang; Junchao Ma; Tingting Wang; Chao Qin; Xiaojie Hu; Ahmed Mosa; Wanting Ling (Chemosphere, 2023)

Conductive black carbon promoted biotransformation of undissolved 2, 2′-dinitrobiphenyl by mediating electron transfer - Hefei Wang; Zeming Wang; Jibao Deng; Jian Wang; Yanzheng Gao (Science of The Total Environment, 2023)

Safety of benzophenone-type UV filters: A mini review focusing on carcinogenicity, reproductive and developmental toxicity - Junchao Ma; Zeming Wang; Chao Qin; Tingting Wang; Xiaojie Hu; Wanting Ling (Chemosphere, 2023)

Implanting nitrogen-doped graphene quantum dots on porous ultrathin carbon nitride for efficient metal-free photocatalytic hydrogen evolution - Hanxiang Chen; Zhao Mo; Zeming Wang; Pengcheng Yan; Peipei Sun; Guanyu Wu; Jinyuan Zhang; Xianglin Zhu; Liang Wang; Hui Xu (Journal of Environmental Chemical Engineering, 2023)

Lead single atoms anchored on reduced graphene oxide as multifunctional additive for lead–carbon battery - Daiwen Tao; Xiong Liu; Zeming Li; Hui Yang; Jinyu Wang; Qilong Zhang (Chemical Engineering Journal, 2023)

Acute effects of three surface-modified nanoplastics against Microcystis aeruginosa: Growth, microcystin production, and mechanisms - Xiaowei Zheng; Liangliang Zhang; Chao Jiang; Jue Li; Yanyao Li; Xianglin Liu; Chengwei Li; Zeming Wang; Nan Zheng; Zhengqiu Fan (Science of The Total Environment, 2023)

Ships’ Small Target Detection Based on the CBAM-YOLOX Algorithm - Yuchao Wang; Jingdong Li; Zeming Chen; Chenglong Wang (Journal of Marine Science and Engineering, 2022)
In order to solve the problem of low accuracy of small target detection in traditional target detection algorithms, the YOLOX algorithm combined with Convolutional Block Attention Module (CBAM) is proposed. The algorithm first uses CBAM on the shallow feature map to better focus on small target information, and the Focal loss function is used to regress the confidence of the target to overcome the positive and negative sample imbalance problem of the one-stage target detection algorithm. Finally, the Soft Non-Maximum Suppression (SNMS) algorithm is used for post-processing to solve the problem of missed detection in close range ship target detection. The experimental results show that the average accuracy of the proposed CBAM-YOLOX network target detection is improved by 4.01% and the recall rate is improved by 8.81% compared with the traditional YOLOX network, which verifies the effectiveness of the proposed algorithm.

Relative reinforcing effects of dibutylone, ethylone, and N-ethylpentylone: self-administration and behavioral economics analysis in rats - Miaojun Lai; Dan Fu; Zeming Xu; Han Du; Huifen Liu; Youmei Wang; Peng Xu; Wenhua Zhou (Psychopharmacology, 2022)

Genome‐wide identification of the traf gene family in yellow catfish ( Pelteobagrus fulvidraco ) and analysis of their expression in response to bacterial challenge - Zhiwei Nie; Bo Wang; Zhixuan Zhang; Zeming Jia; Runjie Xu; Heyu Wang; Wei Zhou; Yifu Gong (Journal of Fish Biology, 2022)
Tumour necrosis factor (TNF) receptor‐associated factor (TRAF) is a receptor protein that has important functions in the immune system. Nonetheless, there have been few reports of traf genes in teleost fishes. The present study aimed to identify the traf genes from the genomic information of yellow catfish ( Pelteobagrus fulvidraco ). Eight traf genes were identified and named, which are distributed on different chromosomes but have similar conserved protein domains. Phylogenetic and syntenic analyses demonstrated conservation of traf genes during evolution. In addition, yellow catfish has the relatively rare traf1 and traf5 genes. Gene structure and motif analysis revealed the homology and distribution diversity of the traf genes. Quantitative real‐time reverse transcription PCR was used to study the expression patterns of traf genes in healthy fish tissues and after infection by Aeromonas hydrophila . The results demonstrated significant changes in traf gene expression, indicating a potential role in innate immunity.

Ammonium Impacts on Vibrations of Hydroxyl and Lattice of Phengite at High Temperature and High Pressure - Weihua Huang; Yan Yang; Zeming Qi; Wendi Liu; Zhongping Wang; Yan Liu; Qunke Xia (Journal of Earth Science, 2021)

Urban trees in university campus: structure, function, and ecological values - Xueyan Wang; Yanlin Wang; Xiaohan Qu; Bing Huang; Zeming Li; Junjiao Sun; Xiaoqing Wei; Xiuying Yang (Environmental Science and Pollution Research, 2021)

Construction and application of a comprehensive coordination and cross-efficiency sustainable development evaluation model: a case study of 31 provinces and regions in China - Guowei Che; Zeming Wang; Zhengli Yang (Environment, Development and Sustainability, 2021)

Space target detection in optical image sequences for wide-field surveillance - Dan Liu; Xiaodong Wang; Yunhui Li; Zeming Xu; Jianing Wang; Zhonghui Mao (International Journal of Remote Sensing, 2020)

Uranium sorption onto mullite: Characteristics of isotherms, kinetics and thermodynamics - Liao Rong; Shi Zeming; Hou Yun; Zhang Kailiang; Zhang Junji; Wang Xinyu; Cheng Ke; Yang Lvhang (Journal of Earth System Science, 2019)

Pressure-dependent Raman spectra of Ba5(PO4)3Cl alforsite - Shuangmeng Zhai; Zeming Li; Sean R. Shieh; Ching-Pao Wang; Weihong Xue (Physics and Chemistry of Minerals, 2018)

Maternal doubled haploid production in interploidy hybridization between Brassica napus and Brassica allooctaploids - Shaohong Fu; Liqin Yin; Mingchao Xu; Yun Li; Maolin Wang; Jin Yang; Tingdong Fu; Jisheng Wang; Jinxiong Shen; Asif Ali; Qiong Zou; Bin Yi; et al. (Planta, 2018)

Detection of inherited mutations for hereditary cancer using target enrichment and next generation sequencing - Yanfang Guan; Hong Hu; Yin Peng; Yuhua Gong; Yuting Yi; Libin Shao; Tengfei Liu; Gairui Li; Rongjiao Wang; Pingping Dai; Yves-Jean Bignon; Zhe Xiao; et al. (Familial Cancer, 2015)

Pharmacokinetics of the main compounds absorbed into blood after oral administration of Liu Wei Di Huang Wan, a typical combinatorial intervention of Chinese medical formula - Ning Zhang; Lijing Li; Ping Wang; Hui Sun; Zeming Wu; Chengyu Piao; Xijun Wang (Journal of Natural Medicines, 2013)

Individual and combined effects of MDM2 SNP309 and TP53 Arg72Pro on breast cancer risk: an updated meta-analysis - Hongtao Cheng; Biao Ma; Ran Jiang; Wei Wang; Hui Guo; Na Shen; Dapeng Li; Qunzi Zhao; Rui Wang; Pengfei Yi; Yue Zhao; Zeming Liu; et al. (Molecular Biology Reports, 2012)

Channelized fluids in subducted continental crust: constraints from δD–δ 18 O of quartz and fluid inclusions in quartz veins from the Chinese Continental Scientific Drilling Project - Xiaoming Sun; Li Xu; Weidong Sun; Wei Zhai; Yeheng Liang; Qian Tang; Jinlong Liang; Zeming Zhang; Kun Shen; Fangyue Wang; Mingxing Ling; Robert E. Zartman (International Geology Review, 2011)